Experimental and Numerical Modeling for the Impact of Freezing Temperatures Reduction on the Mechanical Properties of Frozen Sand - Hasan, Wisam R.; Karim, Hussein H.; Al-Wakel, Saad F. (Salehan Institute of Higher Education, 2025)
Artificial ground freezing (AGF) is an approach that uses heat extraction to congeal in situ soil to improve soil quality temporarily. This technology is ecologically sustainable and has minimal adverse effects on soil and groundwater. AGF is widely used in subterranean construction, providing temporary support and groundwater sealing. Nevertheless, precisely simulating the mechanical characteristics of frozen soils with dependable constitutive models presents significant challenges for scientists and engineers. Frozen soil, consisting of ice, liquid water, solid particles, and pore air, is a distinctive geological substance with heightened sensitivity to temperature and external influences. Experimental studies have shown that the mechanical properties of frozen soils are significantly influenced by temperature, confining pressure, strain rate, stress path, and stress level. Numerical simulation offers a superior approach for forecasting soil qualities, particularly in artificial frozen soil technologies for excavations like tunnels and mines. This research examines the impact of varying freezing temperatures and pressures on soil characteristics. This research employs experiments and numerical analysis using Mohr-Coulomb and hardening soil models. The experimental results indicated that the elastic modulus almost increases linearly by a rate of 90000 kN/m² with 1ºC drops below 0ºC. The unconfined compressive strength increased by 2068 kN/m² for each 1°C decrease from 0 to -2°C. Within the temperature range of -2°C to -10°C, the rate of increase is 529 kN/m². The apparent cohesion increased by 238.75 kN/m² for each 1°C decrease from 0 to -2°C. Within the temperature range of -2°C to -10°C, the rate of increase is 66.25 kN/m². A nonlinear association between temperature decrease and tensile stress rise was observed. Numerical analysis shows that as confined pressure increases and temperature decreases, materials can either get stronger or weaker; the Mohr-Coulomb and HS models show stress-strain curve behavior that matches what was found in experiments.